Effects of Paraquat-induced oxidative stress on antioxidants and Chlorophyll Fluorescence in stay-green wheat (Triticum aestivum L.) flag leaves (Bangladesh Journal of Botany, 2014)
Paraquat, a highly toxic herbicide, induces the production of reactive oxygen species in the cell. Paraquat resistance in stay-green wheat (Triticum aestivum L.) was investigated. Two cultivars, CN12 and CN17, were found to have a higher photo-oxidative resistance than that of common wheat MY11, as measured with antioxidant indexes and chlorophyll a fluorescence. The flag leaves of both CN12 and CN17 maintained a relatively high antioxidant enzyme activity, chlorophyll content, and photosynthetic index and a low level of lipid degradation after 24 h of treatment with 10 ?M paraquat. The Stay-green wheat cultivars CN12 and CN17 had a high resistance to paraquat-induced photo-oxidative stress, which can potentially alleviate some of the damage induced by environment pollution. DOI: http://dx.doi.org/10.3329/bjb.v42i2.18025 Bangladesh J. Bot. 42(2): 239-245, 2013 (December)